DIALEKTIKA ISLAM DAN BUDAYA JAWA DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN ISLAM STUDI ATAS PRAKTIK DA’WAH SUNAN KALIJAGA - Shohib B; Ekaningrum, Ifada Retno; Kholiludin, Tedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the dialectic between Islam and Javanese culture through the perspective of Islamic educational sociology, focusing on the preaching practices of Sunan Kalijaga. Sunan Kalijaga's preaching displayed a unique dialectical strategy, namely integrating Islamic values into local Javanese traditions without causing cultural resistance. Through art forms such as wayang kulit (leather puppet theater), gamelan (traditional orchestra), and Javanese songs, Sunan Kalijaga successfully turned da'wah into a process of social education that instilled religious values while strengthening the cultural identity of the community. An analysis of Islamic educational sociology shows that this culture-based da'wah serves as a means of socializing values, forming collective identity, and providing effective non-formal education in shaping the religious behavior of Javanese society. The dialectic between Islam and Javanese culture offered by Sunan Kalijaga has given rise to a model of Islamic education that is contextual, inclusive, and multicultural, relevant to facing the challenges of modernization and globalization of Islamic education in the contemporary era.